2017
DOI: 10.30958/ajs.4-2-3
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Relationship between Energy Consumption and Urban Form

Abstract: A large proportion of energy demand comes from urban areas, mostly from buildings and transport, the use of which has impacts on climate and air quality through the emissions of greenhouse gases and other pollutants. The research in this paper investigates the relationship between the selected urban form characteristics and energy consumption in England, in order to understand how one influences the other. The influence of urban form is recognized in many aspects of cities, such as human behavior and transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…Apparently, the exponent β R1 = 0.78 from Equation (8) is different from the exponent value of 0.5 in Equation 7, which represents the square root. Moreover, β R0 = 0.44 is different but in the same order of magnitude than 2/ √ N = 0.286 from Equation (7). The goodness of fit of the model in Equation (8) with R 2 = 0.69 is marginally higher with respect to the model in Equation (7).…”
Section: The Relation Between Population Density and Transport Energymentioning
confidence: 75%
See 2 more Smart Citations
“…Apparently, the exponent β R1 = 0.78 from Equation (8) is different from the exponent value of 0.5 in Equation 7, which represents the square root. Moreover, β R0 = 0.44 is different but in the same order of magnitude than 2/ √ N = 0.286 from Equation (7). The goodness of fit of the model in Equation (8) with R 2 = 0.69 is marginally higher with respect to the model in Equation (7).…”
Section: The Relation Between Population Density and Transport Energymentioning
confidence: 75%
“…The goodness of fit of the model in Equation (8) with R 2 = 0.69 is marginally higher with respect to the model in Equation (7). These minor differences are not surprising, given the simplifying assumptions made during the derivation of Equation (7). The results of the two models are plotted in Figure 3.…”
Section: The Relation Between Population Density and Transport Energymentioning
confidence: 93%
See 1 more Smart Citation
“…Osorio et al [11] investigated the relationship between selected urban form characteristics and energy consumption in England, in order to understand how one influences the other. This analysis suggested that better energy efficiency is achieved by areas with higher population density, which provides new insights to urban policy-makers and planners seeking to design strategies to cut carbon emissions and energy consumption.…”
Section: Literature On Urban Form and Energy Usementioning
confidence: 99%
“…Possible applications, advantages and disadvantages of these technologies are explained in de Almeida, Patrão [19], (pp. [9][10][11][12][13][14][15]. Choices between the use of hydraulic and geared traction technology cannot be clearly defined at urban scale without the detailed data.…”
Section: Lift Characteristicsmentioning
confidence: 99%